Positive state observer for the automatic control of the depth of anesthesia—Clinical results. (April 2019) - Nogueira, Filipa N.; Mendonça, T.; Rocha, P.
Highlights: Positive state observer was designed for control law. Controller–observer scheme was implemented in patients during surgical procedures. Control law performed in practice as theoretically expected. Good clinical performance under a variety of clinical situations. Abstract: The depth of anesthesia (DoA) is a crucial feature in general anesthesia. Nowadays the DoA is usually evaluated by the bispectral index (BIS). According to the surgical procedure, different reference levels for the BIS may be clinically required. This can be achieved by the simultaneous administration of an analgesic (e.g. remifentanil ) and an hypnotic (eg propofol ). As a contribution to the effort of automating the processes of drug delivery in general anesthesia, in this paper, a positive state observer is designed for the implementation of a control scheme proposed for the automatic administration of propofol and of remifentanil, in order to track a desired level for the BIS. It is proved and illustrated by simulations that the controller–observer scheme has a very good performance. This scheme was implemented, tested and evaluated both by means of simulations and for a set of patients during surgical procedures.